TEACHING READING IN ESL - Irawati, Iisrohli; Oktiasari, Lini (MAGISTRA, 2013)
Teaching Reading includes many aspects. Teachers must know about some points or unsure in order to be able to teach reading well. By knowing some importance points reading will be taught easily by the teacher.  Success reading should pay attention some aspects of reading itself This paper is supposed to give teachers understanding some importance points of teaching reading. It will show the teacher about some importance points in supporting reading ability, so that the teacher easy to make the students understand the reading easily. This result of paper showed that in teaching reading of ESL the teacher should use the appropriate way to teach the lesson of reading become effective in the class in order that the teaching-learning process can reach the goal of the teaching-learning process itself. Key words: teaching, reading, ESL